A high incidence of BRCA1 mutations in 20 breast-ovarian cancer families. - Serova, O. (1996)
We have analyzed 20 breast-ovarian cancer families, the majority of which show positive evidence of linkage to chromosome 17q12 for germ-line mutations in the BRCA1 gene. BRCA1 mutations cosegregating with breast and ovarian cancer susceptibility were identified in 16 families, including 1 family with a case of male breast cancer. Nine of these mutations have not been reported previously. The majority of mutations were found to generate a premature stop codon leading to the formation of a truncated BRCA1 protein of 2%-88% of the expected normal length. Two mutations altered the RING finger domain. Sequencing of genomic DNA led to the identification of a mutation in the coding region of BRCA1 in 12 families, and cDNA analysis revealed an abnormal or missing BRCA1 transcript in 4 of the 8 remaining families. A total of eight mutations were associated with a reduced quantity of BRCA1 transcript. We were unable to detect BRCA1 mutations in 4 of the 20 families, but only 1 of these was clearly linked to BRCA1. It is expected that the majority of clear examples of the breast-ovarian syndrome will be associated with germ-line mutations in the coding region of BRCA1.